Eat for life : the Food and Nutrition Board's guide to reducing your risk of chronic disease - Woteki, Catherine E.; Thomas, Paul R., 1953-; Institute of Medicine (U.S.). Food and Nutrition Board; Institute of Medicine (U.S.). Committee on Diet and Health; National Research Council (U.S.). Committee on Diet and Health (Washington, D.C. : National Academy Press, 1992)
Gives guidelines for a dietary plan to reduce the risk of diet-related chronic diseases.
Introduction -- Guidelines for a new eating pattern -- The food we eat -- Diet and chronic disease in the United States -- Calories, energy balance, and chronic diseases -- Fats, cholesterol, and chronic diseases -- Protein, carbohydrates, and chronic diseases -- Vitamins, minerals, and chronic diseases -- Alcohol, other food substances, and chronic diseases -- Making the change to the new eating pattern -- Appendixes.
Based on: Diet and health / Committee on Diet and Health, Food and Nutrition Board, Committee on Life Sciences, National Research Council.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Nutrition; Chronic diseases -- Prevention; Chronic diseases; Diet in disease; Chronic Disease; Diet; Nutritional Physiological Phenomena; Nutrition; Maladies chroniques; Régimes alimentaires; HEALTH & FITNESS -- Nutrition; HEALTH & FITNESS -- Diets; MEDICAL -- Nutrition; MEDICAL -- Nursing -- Nutrition; HEALTH & FITNESS -- Food Content Guides; Diet in disease; Chronic diseases; Chronic diseases -- Prevention; Nutrition